Development E-Insurance Based on the Provisions of the Insurance Policy for the Certainty of Evidentiary Civil Procedural Law in Indonesia - Lukman Ilman Nurhakim; Erni Rohaini; Toto Tohir Suriatmadja (GoAcademica Research & Publishing, 2022)
The development of E-Insurance in its match was a development of the Electronic Insurance Policy Agreement or Jo. E-Polis. The insurance agreement or written policy as stipulated by OJK Regulation on Insurance Products and Insurance Product Marketing as an rationing of the Code of Commercial as a special norm of the understanding of Insurance Policy. Unlike the Electronic Insurance Policy Agreement or E-Polis was accommodated by OJK Regulation on Insurance in 2015, E-Insurance developed as a result of insurance needs for electronic or e-commerce trading transactions that do not yet had special arrangements. This was because in E-Insurance, the business’ person did not make hardcopy either the Insurance Policy Agreement or the policy agreement to be further conveyed to the customer or the insured. Furthermore, the Evidentiary Power E-Insurance in the Civil Procedural Law could not be equated: as a means of proof of letter because the parties in the proof cannot show the original (hardcopy). At least judges under Article 10 of the Court of Justice Power Act could categorize E-Insurance as a means of proof of guessing, because the parties in the evidence could not show the original (hardcopy). Thus, a law-level rule was required a law that can accommodate E-Insurance related to proof of civil justice.